2023
DOI: 10.1101/2023.02.03.526931
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parameter variability makes a major contribution to uncertainty of crop phenology simulations

Abstract: Crop phenology has a major influence on crop yield and is a major aspect of crop response to global warming. Process-based models of phenology are often used to predict the effect of weather on the development rate of crops through their growth phases, but such models are associated with large uncertainties, as demonstrated by the large variability between simulation results of different models. The purpose of this study is to estimate the relative importance of model structure uncertainty (due to uncertainty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…However, a recent study pointed out that those previous studies assume that there is a fixed set of parameters to estimate, while in fact there is also considerable uncertainty in the choice of parameters to estimate. Taking into account the uncertainty in choice of parameters, it was found that parameter uncertainty in most cases contributed more, often much more, than model structure uncertainty to overall variability in simulations (Wallach et al, 2023a).…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study pointed out that those previous studies assume that there is a fixed set of parameters to estimate, while in fact there is also considerable uncertainty in the choice of parameters to estimate. Taking into account the uncertainty in choice of parameters, it was found that parameter uncertainty in most cases contributed more, often much more, than model structure uncertainty to overall variability in simulations (Wallach et al, 2023a).…”
Section: Introductionmentioning
confidence: 99%